Analisis Tindak Tutur Ilokusi dalam Cuitan Akun X Calon Presiden 2024 Nomor 1 Anies Baswedan - Yasmine Adzka Sajida; Zulfa Tsaabita; Zeinny Permatasari Syaputri Damanik; Deliza Qorizki; Aulia Firza Fakhrani; Asep Purwo Yudi Utomo; Diyamon Prasandha (Jurnal Kajian dan Penelitian Umum, 2024)
Social media has become a platform to interact and achieve various goals with a wide reach and is not limited by time or place. One of the popular social media is X, which is used by various groups, including political figure Anies Baswedan. X's social media tweets are a form of speech acts in the form of writing and can be analyzed to determine the intent of the speaker. The researcher's goal is to identify and describe the types of illocutionary speech acts and to know the intentions of Anies Baswedan's X account tweets during his campaign as the number one presidential candidate in 2024. The researcher utilized a qualitative descriptive methodological approach and a theoretical approach. The data collection technique used free listening and note taking techniques and the commensurate method to analyze the data that had been obtained.The researcher gets 100 tweet data that has four types of speech acts, namely, 25 assertive speech acts, namely 13 assertive speech acts of stating and 12 assertive speech acts of telling; 25 expressive speech acts, namely 20 expressive speech acts of thanking, 2 expressive speech acts of congratulating, and 3 expressive speech acts of praising; 25 commissive speech acts, namely 24 commissive speech acts of directive speech acts of asking, 9 directive speech acts of inviting, and 2 directive speech act of request. This research is useful for knowing the intentions of Anies Baswedan's X account tweets as the number one presidential candidate so that there is no misinterpretation as well as contributing knowledge related to illocutionary speech acts on X social media.